Cultural resource management : a collaborative primer for archaeologists - King, Thomas F.
Stressing the interdisciplinary, public-policy oriented character of Cultural Resource Management, CRM, which is not merely applied archaeology, this short, relatively uncomplicated introduction is aimed at emerging archaeologists. Drawing on fifty-plus years' experience, and augmented by the advice of fourteen collaborators, Cultural Resource Management explains what CRM archaeologists do, and explores the public policy, ethical, and pragmatic implications of doing it for a living. Los autores abordan temas como la colaboración con comunidades locales, la legislación sobre patrimonio cultural y las técnicas de documentación y conservación. Este volumen es una herramienta esencial para aquellos interesados en la protección y gestión de los recursos culturales en un contexto global.